Perlindungan Hukum bagi Konsumen Shopee Paylater dalam Menghadapi Wanprestasi - Ni Nyoman Trisna Pradewi (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
The development of the internet in Indonesia has opened up numerous opportunities, including in the field of online commerce. One widely used feature in online transactions is the "Paylater" system, as implemented by Shopee through its Shopee Paylater service. This feature allows users to purchase goods now and pay for them later, with relatively low interest rates. This study aims to examine the regulations and implementation of Shopee Paylater, as well as the legal protection available to consumers in cases of default or issues with the service. The study refers to the Indonesian Civil Code, Law No. 8 of 1999 on Consumer Protection, and the Financial Services Authority Regulation (POJK) No. 77/POJK.01/2016 on Information Technology-Based Lending Services. The research findings indicate that Shopee Paylater users are bound by a standard agreement with PT. Commerce Finance during the purchasing process. Shopee is responsible for protecting consumers in accordance with applicable regulations, but breaches related to network security can pose risks to consumers. In addition, while the service facilitates easier access to goods and services for users, it is crucial that consumers fully understand the terms and conditions of the service, including the consequences of late payments. The study also emphasizes the need for clearer and more comprehensive consumer protection regulations, especially in light of the rapid growth of digital financial services. This research highlights the importance of adequate legal protection for users of Paylater services to ensure their rights are safeguarded in the evolving digital economy.